Water-based barrier coating containing sodium bentonite and preparation method thereof

By using high-shear mixing of unmodified sodium-based bentonite with water-based adhesives to form a water-based barrier coating, the environmental problems of traditional coatings are solved, achieving high-efficiency barrier performance and low load, making it suitable for paper-based packaging materials.

CN120936550APending Publication Date: 2025-11-11SPECIALTY MINERALS MICHIGAN INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480020455.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-24
Filing Date
2024-03-22
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

The barrier coatings of existing paper-based packaging materials mainly rely on petroleum-based materials, resulting in poor recyclability and non-biodegradability, making it difficult to meet environmental protection requirements. At the same time, the peeling process of traditional nano-clay is complex and energy-intensive.

Method used

Unmodified sodium-based bentonite is mixed with a water-based binder, and the sodium-based bentonite is dispersed in the binder through high-shear mixing technology, maintaining the form of crystalline aggregates to form a water-based barrier coating.

Benefits of technology

It achieves high barrier performance, reduces the loading level of sodium bentonite, avoids the use of dispersants, and exhibits barrier properties comparable to multilayer coatings in single-layer coatings, making it suitable for porous substrates such as paper and paperboard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005604534700000081
    Figure BDA0005604534700000081
  • Figure BDA0005604534700000101
    Figure BDA0005604534700000101
  • Figure HDA0005604534710000011
    Figure HDA0005604534710000011
Patent Text Reader

Abstract

An aqueous barrier coating for a paper product can include a chemically unmodified sodium bentonite dispersed in a binder, where the sodium bentonite is dispersed under high shear conditions such that the sodium bentonite is present in the form of crystalloid agglomerates.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-application of related applications

[0002] The benefit of priority to U.S. Provisional Patent Application No. 63 / 454,536, filed March 24, 2023, is claimed herein, and the disclosure thereof is incorporated herein by reference in its entirety. Technical Field

[0003] This disclosure relates to water-based barrier coatings and methods for preparing water-based barrier coatings containing sodium-based bentonite. Background Technology

[0004] Paper-based packaging materials are used worldwide. Currently, barrier coatings for paper and packaging applications primarily rely on petroleum-based materials and synthetic polymers such as waxes, polyvinyl alcohol, and polyolefins (Gironi and Pietmonte, 2011). These materials are cost-effective, readily available, and provide important barriers against water vapor, oil / grease, and oxygen for packaging applications. However, these materials have significant drawbacks, such as poor recyclability and non-biodegradability of coated paper, which can have adverse environmental impacts. In the context of food packaging, ideal packaging materials must possess good barriers against oxygen, water vapor, and oil / grease, while being derived from bio-based, recyclable, compostable, and / or other environmentally friendly sources. Barrier property requirements can vary depending on the coating application and the end use of the paper product.

[0005] Nanoclays have been used in a variety of applications and are generally advantageous due to their ability to swell in water. Sun et al. reported a nanoclay / latex composite for improving barrier properties in coatings. See Sun et al., *Compos. Science & Technology* 67 (2007) 1823-1829. Consistent with the traditional expectations and uses of nanoclays, Sun et al. taught that the nanoclay must be fully exfoliated in the coating and that cationic surface modification of the clay and / or the use of dispersants are necessary. Specifically, Sun concluded that the barrier properties of polymer / clay nanocomposites depend heavily on the degree of exfoliation of the nanoclay layer and that sufficient exfoliation is necessary to obtain good barrier performance. Summary of the Invention

[0006] According to this disclosure, a method for preparing an aqueous barrier coating for a paper substrate may include: mixing a chemically unmodified dry powder of sodium bentonite with a binder; and subjecting the mixture to high-shear mixing under conditions that disperse the sodium bentonite in the binder and at least a portion of the sodium bentonite remains in a crystalline aggregate form, thereby forming the barrier coating. The binder may be water-based or water-soluble.

[0007] According to this disclosure, a method for preparing an aqueous barrier coating for a paper substrate may include: mixing a chemically unmodified dry powder of sodium bentonite with a polymer latex binder; and subjecting the mixture to high-shear mixing under conditions that disperse the sodium bentonite in the polymer latex and at least a portion of the sodium bentonite remains in the form of crystalline aggregates, thereby forming the barrier coating.

[0008] The method according to this disclosure may further include applying the barrier coating to the paper substrate.

[0009] According to this disclosure, an aqueous barrier coating may include unmodified sodium bentonite dispersed in an adhesive, wherein the sodium bentonite is dispersed under high shear conditions such that the sodium bentonite exists in the form of crystalline aggregates.

[0010] The coating may be free of dispersants. Attached Figure Description

[0011] Figure 1 It is a graphic illustrating the liquid water resistance of paper with a barrier coating applied by Water Cobb.

[0012] Figure 2 This is a graph showing the water vapor transmission rate of the barrier coating under thermal conditions of 90% RH and 38°C.

[0013] Figure 3 These are photographs of the oil barrier properties of the coating tested according to this disclosure.

[0014] Figures 4A to 4D It is a particle size distribution diagram of sodium-based bentonite for coating according to this disclosure.

[0015] Figure 5 The scanning electron microscope image of the coating according to this disclosure shows the presence of sodium-based bentonite crystalline aggregates in the coating.

[0016] Figure 6 The graph shows the water vapor transmission performance of the coating according to this disclosure and conventional coatings as a single-layer coating and tested under thermal conditions.

[0017] Figure 7 The graph shows the water vapor transmission performance of the coating according to this disclosure and a conventional coating, which are formed as a double-layer coating and tested under thermal conditions. Detailed Implementation

[0018] The water-based coating according to this disclosure comprises chemically unmodified sodium bentonite dispersed in a binder to advantageously provide a water-based barrier coating. It has been advantageously found that the barrier coating properties can be achieved by incorporating dried sodium bentonite, wherein the sodium bentonite used as a raw material in the coating is in its natural hydrophilic state and is not exfoliated. The exfoliation of the sodium bentonite can be carried out under high-shear mixing conditions used in dispersing the sodium bentonite in the binder during the preparation of the coating of this disclosure. Advantageously, no pretreatment of the sodium bentonite is required prior to dispersion in the binder.

[0019] The coating disclosed herein comprises chemically unmodified sodium bentonite dispersed in a binder using high-shear mixing conditions, such that at least a portion of the sodium bentonite exists in the coating as a crystalline aggregate. Figure 5 The SEM image of the coating disclosed herein shows the presence of crystalline aggregates in the coating. The coating disclosed herein may be a water-based barrier coating.

[0020] The method for preparing a water-based barrier coating according to this disclosure may include: mixing a chemically unmodified dry powder of sodium bentonite with a binder, and subjecting the mixture to high-shear mixing under conditions that disperse the sodium bentonite in the binder and at least a portion of the sodium bentonite remains in the form of crystalline aggregates.

[0021] As used herein, “sodium bentonite” refers to bentonite having at least 50% sodium cations. The sodium bentonite used in the methods and coatings of this disclosure is chemically unmodified sodium bentonite and optionally may be mechanically unmodified. As used herein, “mechanically unmodified sodium bentonite” refers to sodium bentonite that may or may not have sodium ion exchange, but has not undergone mechanical shearing prior to incorporation into the coating and retains its natural hydrophilic state. As used herein, “chemically unmodified sodium bentonite” refers to sodium bentonite that may or may not have sodium ion exchange, but has not undergone chemical modification such as with organic modifiers. In some coatings of this disclosure, the sodium bentonite mixed with the binder is chemically and mechanically unmodified and optionally peeled during dispersion in the binder, thereby modifying the sodium bentonite present in the final coating by mechanical shearing. In some coatings of this disclosure, the sodium bentonite mixed with the binder is chemically unmodified. In some of the coatings disclosed herein, the sodium-based bentonite is chemically unmodified. Figures 4A to 4D The particle size distribution of unmodified sodium-based bentonite that can be used in the coatings and methods of this disclosure is shown.

[0022] The sodium bentonite used in the coatings and methods disclosed herein can have a moisture content of less than about 12%. The sodium bentonite is incorporated into the binder of the coating in a dry granular or powdered state, without pre-expansion or peeling, and dispersed in the binder using high-shear mixing. High-shear mixing conditions can be selected and customized to provide peeling of the sodium bentonite while dispersing it in the binder. It has been found that using sodium bentonite peeled during dispersion results in a high shape factor sodium bentonite in the final coating. As used herein, a high shape factor refers to a shape factor greater than 4, such as that measured by Horizontal scattering. 50 The ratio of the Zave particle size was measured using dynamic light scattering. Advantageously, it was found that exfoliation during dispersion within the binder increased the shape factor of the sodium bentonite while allowing a portion of the sodium bentonite to remain in a crystalline aggregate form.

[0023] The sodium-based bentonite may contain at least about 60%, at least about 65%, at least about 70%, at least about 75%, or at least about 80% montmorillonite.

[0024] It has been observed that in the coatings of this disclosure, at least a portion of the sodium-based bentonite retains a crystalline aggregate form. Surprisingly, improved barrier coating properties have been achieved without completely stripping the sodium-based bentonite; instead, at least a portion of the sodium-based bentonite retains a crystalline aggregate form. Figure 5 Crystalline aggregates of sodium bentonite retained in the coating were demonstrated. It has been observed that using sodium bentonite in dry powder form combined with high-shear mixing for dispersing sodium bentonite in the binder allows sodium bentonite to be incorporated into the coating, resulting in the presence of crystalline aggregates and dispersion in the binder.

[0025] Compared to conventional coatings containing talc and kaolin, the coatings of this disclosure have been observed to achieve improved barrier properties. Compared to coatings containing talc or kaolin, the coatings of this disclosure achieve comparable barrier coating properties, even without improvement, and significantly reduce the loading level of sodium-based bentonite. Furthermore, the coatings of this disclosure can be formed without the addition of dispersants.

[0026] High-shear mixing conditions are used to disperse sodium bentonite in a binder, resulting in a coating in which at least a portion of the sodium bentonite exists in the form of crystalline aggregates. Such high-shear mixing can be achieved, for example, by mixing at a tip speed of about 655 ft / min to about 3300 ft / min (200 m / min to 1010 m / min). High-shear mixing can be performed using any known method or combination of methods (including, but not limited to, using a Cowles mixer, ultrasonic treatment, and rotor-stator mixing). High-shear mixing may include, for example, ultrasonic treatment lasting at least 1 minute. The ultrasonic treatment time can be about 1 minute to about 40 minutes, about 10 minutes to about 30 minutes, or about 5 minutes to about 25 minutes. Other suitable times include approximately 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, and 40 minutes, along with values ​​within these ranges and the ranges defined by those values. For example, high shear can be applied under conditions intended to reduce or prevent overheating. For instance, ultrasonic treatment can be performed using a jacketed vessel with water circulation and a pulsed method to prevent overheating.

[0027] High-shear mixing processes allow sodium bentonite to exfoliate during dispersion within the binder, while also allowing the crystalline aggregate form of sodium bentonite to remain in the coating. Therefore, the shape factor of the sodium bentonite in the coating can be increased compared to the starting material before dispersion. The shape factor of the dispersed sodium bentonite can, for example, be greater than 4. The shape factor referenced herein is the Horibad shape factor using static light scattering. 50 The measurement results are compared with the Zave size, as measured by dynamic light scattering. It has been observed that sodium-based bentonite with a shape factor greater than 4 can be obtained by high-shear mixing with binders, such as by ultrasonic treatment for 5 minutes or longer, or by using a rotor-stator shearing device.

[0028] The coating can include any suitable water-based adhesive. For example, the adhesive can be a water-based polymer latex. Non-latex adhesives can also be used. For example, the adhesive can be one or more of anionic polymer latexes, such as styrene-butadiene, polyolefins, styrene-acrylates, ethylene-acrylic acid copolymers, ethylene-vinyl alcohol copolymers, polyurethanes, epoxy resins, polyesters, polyolefins, carboxylated styrene-butadiene latex, carboxylated styrene-acrylate latex; polyvinylidene chloride; polyvinyl chloride; starch; styrene-acrylic acid copolymers; styrene-maleic anhydride; polyvinyl alcohol; polyvinyl acetate; carboxymethyl cellulose; silicone; wax; chloroprene rubber; polyhydroxy ethers; varnishes; polylactic acid; polylactic acid copolymers; fluorine-containing polymers; acrylonitrile copolymers; and carboxylated styrene-butadiene-acrylonitrile copolymers.

[0029] Sodium bentonite may be added to the binder in amounts of about 1 wt% to about 20 wt%, about 1 wt% to about 5 wt%, about 3 wt% to about 15 wt%, or about 10 wt% to about 20 wt% based on the total weight of the coating on a dry weight basis. Other suitable amounts include about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20 wt% based on the total weight of the coating on a dry weight basis, and any values ​​therein and any ranges defined by such values. Unless otherwise stated, references to the percentage (%) of sodium bentonite in coatings of this disclosure refer to weight percentages based on the total weight of the coating on a dry weight basis. The loading level of sodium bentonite can be significantly lower than that required for talc or kaolin in conventional coatings while maintaining or even exhibiting improved barrier properties. For example, the sodium bentonite load in the coating of this disclosure may be 1 / 60 to 1 / 2 of the load required for other barrier coatings based on platy minerals (such as talc or kaolin coatings).

[0030] The coatings disclosed herein are used for coating porous substrates, such as paper and paperboard. For suitability in such applications, the solids content of the coatings disclosed herein can be from about 5% to about 55%, from about 15% to about 55%, from about 20% to about 40%, from about 30% to about 50%, or from about 10% to about 25%. Other suitable solids contents include about 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, and any values ​​therein and ranges defined by such values.

[0031] The solids content of coatings prepared by dry addition of sodium bentonite can advantageously be equal to or greater than the solids content of the binder. In contrast, the solids content of coatings prepared by wet addition of sodium bentonite is lower than that of the binder due to the presence of liquid in the sodium bentonite slurry.

[0032] The coating disclosed herein can be applied using conventional paper coating methods, such as blade coating, leaf coating, fabric coating, gravure printing coating, roll-to-roll machine coating, pelletizing, reverse roll coating, hot melt coating, flexographic bar coating / flexographic printing coating, transfer coating, die coating, wet film coating machine coating, coating casting using filtration and evaporation, dip coating, and extrusion coating. The substrate can be coated, for example, with any desired coating weight and / or multiple coatings. For example, approximately 1 g / m³ can be coated. 2 Approximately 35g / m 2 Approximately 1g / m 2 Approximately 25g / m 2 Approximately 5g / m 2 Approximately 15g / m 2 The coating weight is the amount of coating applied. For example, the coating weight can be approximately 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, or 35 g / m². 2 And any value therein or the range defined by such values.

[0033] The coating disclosed herein can be a single-layer coating and has a strength of less than 10 g / m². 2 For example, approximately 2g / m 2 to less than 10g / m 2 or approximately 4g / m 2 Approximately 8g / m 2 The coating weight. Other suitable single-layer coating weights may include approximately 1, 2, 3, 4, 5, 6, 7, 8, and 9 g / m². 2 , and any values ​​thereof and the ranges defined by such values. It has been advantageously observed that the beneficial effects of coatings of this disclosure, including sodium bentonite instead of kaolin or talc, can allow for the use of a single-layer coating while achieving the desired barrier properties. This is advantageous because two- or multi-layer coatings may not be practical in many applications, especially when using multifunctional layers / coatings. At the weight of a single-layer coating, the barrier properties exhibited by the coatings of this disclosure are improved by 31% compared to pure latex with the dry addition of 3% sodium bentonite. Compared to competing products containing 40% loading, Barrisurf… TM Compared to comparative coating formulations of LX kaolin, the coating of this disclosure with dry addition of 3% sodium bentonite also showed a 39% improvement. Compared to wet addition, the barrier properties exhibited by dry addition of sodium bentonite in the coating were improved by more than 30%.

[0034] Porous substrates used with the coatings of this disclosure can generally include any paper or paperboard product that requires a barrier coating. Paper substrates on which the coatings of this disclosure can be coated can include, but are not limited to, solid bleached sulfate (SBS) paper, folding boxboard (FBB), white-faced boxboard (WTL), low-basic-weight paper such as fast food packaging paper, copy paper, coated or uncoated paper and paperboard, coated unbleached kraft paper (CUK) and coated recycled paperboard.

[0035] The coating disclosed herein can be customized to provide water vapor permeability or other barrier properties according to the intended application of the paper substrate. For example, the barrier coating can provide <40 g / m² under thermal conditions (38°C and 90% RH). 2 / d Water vapor transmission rate (WVTR), and / or water COBB 60 min <1 g / m 2 In this field, WVTR under thermal conditions is generally considered to be <10 g / m³ for extremely high barrier applications. 2 / d, for high-barrier applications it is <100g / m 2 / d, for medium barrier applications it is 100-400 g / m 2 / d, and for low-barrier conditions it is >400g / m 2 / d. The barrier coating according to this disclosure can be customized for any of the aforementioned applications.

[0036] Example

[0037] Example 1: Dry addition versus wet slurry addition

[0038] Three different methods are used to create the coating formulation. In the first method according to this disclosure, sodium bentonite is added to the latex as a dry powder, which is referred to below as "dry addition". A second comparative method is used, in which the sodium bentonite is prepared into a slurry in water before being added to the latex, which is referred to as "acumer-free". In a comparative third example, a dispersant chemical is first added to water, then dry sodium bentonite powder is added, and finally this pre-dispersed sodium bentonite slurry is added to the latex, which is referred to as "0.08% acumer".

[0039] Dry addition: 5% sodium bentonite added dry.

[0040] The water-based barrier coating according to this disclosure is prepared as follows: 370 g of a material having 52% solids is weighed into a 1000 ml steel container. 1004 Styrene-Butadiene Latex. Add 10.7g of sodium bentonite with 10% moisture and 27.7g of water. Thoroughly mix the resulting slurry for 30 minutes using a Premier Model 2500HV Cowles mixer with 2.5-inch (6.35cm) diameter blades at a tip speed of 2945ft / min. Determine the final solids content of the formulation to be 45% using an oven drying method.

[0041] Acumer-free: Wet addition of 5% sodium bentonite without dispersant

[0042] A slurry of sodium-based bentonite was prepared in water by adding 11.1 g of dry sodium-based bentonite with 10% moisture content to 200 g of water. The suspension was then agitated for 15 minutes at a tip speed of 2945 ft / min using a Premier Model 2500HV Cowles mixer with 2.5-inch (6.35 cm) diameter blades. The solids content of this water-based sodium-based bentonite slurry was determined to be 5% using an oven drying method. This was achieved by adding 370 g of sodium-based bentonite with 52% solids content... 1004 styrene-butadiene latex was mixed with 178.1 g of a sodium-based bentonite slurry with a 5% solids content to prepare a barrier coating formulation in a 1000 ml steel container. The mixture was then stirred for 15 minutes using the same Cowles-type mixer at a tip speed of 2945 ft / min. The final solids content of the formulation was determined to be 45% using an oven drying method.

[0043] 0.08% Acumer: Wet addition of 5% sodium bentonite with dispersant

[0044] A slurry of sodium-based bentonite was prepared in 300 g / m water by adding 0.0608 g of ACUMER 9300 with 45% solids, followed by 38 g of powder with 10% moisture. The mixture was stirred for 15 minutes at a tip speed of 2945 ft / min using a Premier Model 2500HV Cowles mixer with 2.5-inch (6.35 cm) diameter blades. The final solids content of the slurry was determined to be 11% using an oven drying method. To prepare the barrier formulation, 70.4 g of the slurry with 11% solids was added to 304 g of powder with 52% solids. 1004 Styrene-Butadiene Latex. The resulting barrier formulation was stirred for 15 minutes using the same Cowles type mixer at a tip speed of 2945 ft / min.

[0045] coating

[0046] The scraping method was used at 350 g / m 2Barrier coatings were prepared on SBS (Solid Bleached Sulfate) boards. Each board had a double-layer coating with the same formulation, and different coating weights were prepared using rod numbering from 4 to 13. The resulting average coating weight was 13-15 g / m². 2 and 23-25g / m 2 The weights of the two coatings were then measured. The paper coated with the barrier formulation was then tested for liquid water resistance (water Cobb) using TAPPI 441, water vapor transmission rate (WVTR) using TAPPI T 464, and oil and grease barrier properties (OGR) using oil Cobb. The oil Cobb method is a modified version of the TAPPI 441 method for testing OGR. In this procedure, the surface of the barrier-coated paper is covered with saturated oil-absorbing paper for 30 minutes, and then the weight change caused by oil absorption is measured to determine the oil Cobb number. The results of the barrier coating are shown in... Figure 1 , 2 and 3.

[0047] Example 2: Determining the influence of shape factor and mixing conditions on shape factor

[0048] The original, chemically unmodified sodium-based bentonite had a moisture content of 8%, and a dry particle size at least 99.00% finer than 200 mesh (74 micrometers), and a wet particle size at least 99.75% finer than 200 mesh (74 micrometers). The particle size of the dispersed sodium-based bentonite was determined using a Horiba LA950 static light scattering instrument. This was achieved by adding 0.5 g of bentonite powder to a material with a moisture content of 0.005%. A 1.0% bentonite suspension was prepared in 50 ml of DI aqueous solution with a dispersant concentration of 30%. The resulting suspension was sonicated for 8 minutes using a 0.5-inch horn at setting 1.5 to disperse it. The dispersed suspension was added dropwise to a Horiba LA950 cell to achieve a red laser transmittance of 89–91%, and the particle size was determined using standard settings and refractive index for calcium carbonate. This method measures the particle size relative to the relatively large basal plane dimensions of bentonite.

[0049] Undispersed sodium-based bentonite samples were also tested. Aqueous suspensions of sodium-based bentonite with any solids content from approximately 1% to 10% can be prepared, and varying degrees of shear can be applied using any type of mixing or ultrasonic treatment equipment. This suspension was added to a Horiba LA950 tank, and particle size was measured as previously described.

[0050] Table 1

[0051]

[0052] The particle size of sodium bentonite was also determined using dynamic light scattering (DLS) technology on a Malven Zetasizer 1000 instrument. Dispersed or undispersed suspensions can be used. The suspension was diluted to 0.1% solids using DI water. The diluted suspension was transferred to instrument cuvettes (1 cm x 1 cm plastic, all sides transparent) and placed in the instrument's measurement chamber. The particle size and refractive index (1.503) of the sodium bentonite were measured using water as a solvent, according to standard software settings. The resulting Zave value (hydrodynamic diameter) was reported. This instrument is designed to measure nanoparticles, therefore this technique was used to provide a much larger value relative to the relatively small thickness of the sodium bentonite plate. The measured Zave values ​​for sodium bentonite varied between 500 and 1500 nm.

[0053] The shape factor (SF) of bentonite has been determined to be a ratio of two particle size methods—the ratio of the diameter from static light scattering (Horiba LA-950) to the diameter from dynamic light scattering (DLS). For bentonite, sedimentation was observed to be unsuitable due to the extremely long settling time. The shape factor (SF) was calculated by using the ratio of the median particle size (d50) determined by Horiba light scattering to the Zave particle size in micrometers determined using a Malvern Zetasizer 1000 DLS. The resulting SF values ​​for sodium-based bentonite can vary between 3.5 and 7, with higher values ​​indicating greater stratification and higher particle aspect ratios.

[0054] Two samples with high and low SF were prepared as follows:

[0055] Low SF: As in the “Acumer-free” example above, a 5% solid sodium bentonite slurry was prepared in DI water, but in a volume of 500 mL, and high-speed mixing with Cowles was carried out at 2000 rpm for only 5 minutes.

[0056] High SF: Sonicate another 500 mL of 5% solids starting slurry in a water-cooled beaker for a total of 20 minutes, continuously mixing with a propeller stirrer. To avoid heating, cycle the sonication on and off for a total of 20 minutes.

[0057] Table 2

[0058] describe Hor d10 Hor d50 Hor d90 ZS Zave(um) SF(Hd50 / Zave) Cowles 2000rpm, 5 minutes 2.10 4.30 8.23 1.11 3.87 Ultrasonic treatment for 20 minutes 1.13 2.91 9.12 0.548 5.31

[0059] This indicates that mixing methods can be selected to disperse sodium bentonite within a binder to produce a final composition containing sodium bentonite with either a high or low shape factor. High-shear mixing methods (such as ultrasonication) were observed to produce materials with a high shape factor.

[0060] Example 3: The effect of shape factor and dry additives on barrier properties

[0061] Coatings according to this disclosure were prepared using sodium-based bentonite with high and low forming factors, as well as dry-added and wet-added sodium-based bentonite. Chemically unmodified sodium-based bentonite as described in Example 2 was used as the starting material in the coatings of this disclosure. Each coating according to this disclosure comprised 3% sodium-based bentonite by dry weight. The barrier properties of these coatings were compared with each other and with… 1004 (pure latex) coating and containing Barrisurf TM A comparison of the barrier properties of LX (kaolin) coatings.

[0062] By 150g A coating according to this disclosure was prepared by combining 1004 with 2.6 g of dry sodium bentonite powder, containing 3% sodium bentonite with a low shape factor. To create the low shape factor formulation, the mixture was stirred at 2000 RPM for 5 minutes using a Cowles blade with a 2.5-inch diameter. The formulation was diluted to 47% by adding DI water. This formulation was stored overnight, and then the viscosity, pH, and solids were measured.

[0063] By 150g A coating according to this disclosure was prepared by combining 1004 g of dry sodium-based bentonite powder with 2.6 g of sodium-based bentonite powder, containing 3% sodium-based bentonite with a high shape factor. For the high shape factor formulation, the mixture was stirred at 2000 RPM for 5 minutes, then sonicated for 20 minutes using a pulse function, alternating between 30-second on and 30-second off cycles. The pulse function was used to prevent overheating. The formulation was diluted to 47% by adding DI water. This formulation was stored overnight, and then its viscosity, pH, and solids were measured.

[0064] A coating according to this disclosure is prepared by first forming a sodium-based bentonite slurry with a wet addition of 3% sodium-based bentonite having a low shape factor. The slurry is prepared as described in Example 3 for preparing the low-shape-factor sodium-based bentonite slurry. Specifically, 25g of dry sodium-based bentonite powder is mixed with 475g of water and sheared at 2000RPM for 5 minutes using a 2.5-inch Cowles blade to achieve a final bentonite slurry solids concentration of 5%. Subsequently, 150g of… 1004 was mixed with 48.2g of wet 5% sodium bentonite slurry. Then, a propeller-type overhead mixer was used at 800 RPM to... Mix 1004 latex and sodium bentonite slurry for 15 minutes. Store this mixture overnight, then measure viscosity, pH, and solids.

[0065] A coating according to this disclosure with a high shape factor of 3% sodium bentonite was prepared by first forming a sodium bentonite slurry. The slurry was prepared as described in Example 3 for preparing the high shape factor sodium bentonite slurry. Specifically, 25g of dry sodium bentonite powder was mixed with 475g of water and sheared at 2000RPM for 5 minutes using a 2.5-inch Cowles blade. To further achieve a high shape factor, the same formulation was ultrasonically treated with a pulse function for 20 minutes, alternating between 10-second on and 20-second off. The pulse function was used to prevent overheating. The final solids content of the sodium bentonite slurry was 5%. 150g 1004 was mixed with 48.2g of wet 5% sodium bentonite slurry. Then, a propeller-type overhead mixer was used at 800 RPM to... Mix 1004 latex and sodium bentonite slurry for 15 minutes. Store this mixture overnight, then measure viscosity, pH, and solids.

[0066] Preparation of Barrisurf TM LX (kaolin) comparative example coating as 40% Barrisurf TM 1004 preparation. Take 150g... 1004 and 84.4g Barrisurf TM LX slurry mix. Barrisurf TM The LX slurry had a solids content of 61.6%. The mixture was then blended for 15 minutes at 800 RPM using a propeller-type overhead mixer. This formulation was stored overnight, and then its viscosity, pH, and solids were measured.

[0067] For each coating formulation, an automatic coating machine is used to apply the coating to a concentration of 175 g / m² at a speed of 40 m / min. 2 The coating is applied to white-faced cardboard boxes. The coating is dried in an oven at 103°C for 10 minutes, then conditioned in a CTH chamber for 24 hours. Single and double coats are applied. For a single coat, the target coating weight is 5.8 ± 0.4 g / m². 2 For a double-layer coating, the target coating weight is 10.8 ± 0.3 g / m². 2 Subsequently, a ring with a diameter of 7.62 cm was cut and used for WVTR testing under thermal conditions (38°C, 90% RH).

[0068] Table 3 provides the viscosity, pH, and solids content of the prepared coating formulations.

[0069] Table 3

[0070]

[0071] *3% sodium bentonite refers to 3 wt% sodium bentonite based on the total weight of the coating on a dry weight basis.

[0072] Water vapor transmission rate was tested using the TAPPI T 464 (WVTR) method under thermal conditions (38°C, 90% RH). See [link to relevant documentation]. Figure 6 , and only 1004 coating and containing Barrisurf TM Compared to LX (kaolin) coatings, the single-layer coating of this disclosure exhibits a significant improvement in water vapor transmission characteristics. Furthermore, compared to wet addition, dry addition of sodium-based bentonite in the coating of this disclosure also showed improved water vapor transmission performance. Finally, improved water vapor transmission performance was also observed when using a coating formulation process, which resulted in the presence of sodium-based bentonite with a high shape factor in the coating. Specifically, quantitative improvements in the following properties were observed:

[0073] Compared to pure latex, the WVTR of formulations containing 3% high aspect ratio sodium bentonite was reduced by 31%.

[0074] Compared with formulations containing moist high aspect ratio sodium bentonite, formulations containing dry high aspect ratio sodium bentonite have a 36% lower WVTR.

[0075] Compared with formulations containing moist sodium bentonite with low aspect ratio, the WVTR of formulations containing dry sodium bentonite with low aspect ratio was reduced by 32%.

[0076] With Barrisurf TM Compared to LX, the WVTR of the formulation containing 3% dry-added high aspect ratio sodium bentonite was reduced by 39%.

[0077] See Figure 7 When using a double coating, the coating of this disclosure and 1004 and Barrisurf TM The decrease in WVTR between the (kaolin) comparative coatings was not significant. A decrease in water vapor permeability was still observed, particularly with dry addition of sodium-based bentonite. Furthermore, surprisingly and beneficially, it was observed that... 1004 and Barrisurf TM Compared to a two-layer coating, the coating according to this disclosure, with the addition of sodium-based bentonite having a high shape factor, can provide similar or even improved water vapor transmission performance when formed as a single-layer coating. Therefore, the coating of this disclosure avoids the need for a two-layer coating, which may be complex and impractical in some applications, while maintaining at least the same level of barrier properties as a conventional kaolin coating with a two-layer structure.

[0078] The foregoing description is provided for clarity of understanding only, and should not be construed as an unnecessary limitation, as modifications within the scope of this disclosure will be readily apparent to those skilled in the art.

[0079] All patents, patent applications, government publications, government regulations, and references cited in this specification are hereby incorporated herein by reference in their entirety. In case of conflict, this specification (including definitions) shall prevail.

[0080] Throughout this specification, unless otherwise stated, when a compound, composition, method, and / or process is described as comprising components, steps, or materials, it is understood that the compound, composition, method, and / or process may also comprise, consist substantially of, or consist of any combination of said components or materials. Unless otherwise expressly stated, component concentrations may be expressed as weight concentrations. In light of the foregoing disclosure, as will be understood by one of ordinary skill in the art, combinations of components include homogeneous and / or non-homogeneous mixtures.

Claims

1. A method for preparing an aqueous barrier coating for a paper substrate, the method comprising: The dry powder of chemically unmodified sodium-based bentonite is mixed with a binder; and The barrier coating is formed by subjecting the mixture to high shear mixing under conditions that disperse the sodium bentonite in the binder and at least a portion of the sodium bentonite remains in the form of crystalline aggregates, wherein the binder is water-based or water-soluble.

2. The method of claim 1, wherein the adhesive comprises a polymeric latex.

3. The method according to claim 2, wherein the polymer latex is an anionic polymer latex.

4. The method according to claim 3, wherein the anionic polymer latex comprises one or more of the following: styrene-butadiene, polyolefin, styrene acrylate, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyurethane, epoxy resin, polyester, polyolefin, and carboxylated styrene-butadiene.

5. The method according to any one of the preceding claims, wherein the adhesive comprises one or more of the following: carboxylated styrene acrylate latex, polyvinylidene chloride, polyvinyl chloride, starch, styrene-acrylic acid copolymer, styrene-maleic anhydride, polyvinyl alcohol, polyvinyl acetate, carboxymethyl cellulose, silicone, wax, chloroprene rubber, polyhydroxy ether, varnish, polylactic acid, polylactic acid copolymer, fluorine-containing polymer, acrylonitrile copolymer, and carboxylated styrene-butadiene-acrylonitrile copolymer.

6. A method for preparing an aqueous barrier coating for a paper substrate, the method comprising: The dry powder of chemically unmodified sodium-based bentonite is mixed with an aqueous polymer latex binder; and The mixture is subjected to high-shear mixing under conditions that disperse the sodium-based bentonite in the polymer latex and at least a portion of the sodium-based bentonite remains in the form of crystalline aggregates, thereby forming the barrier coating.

7. The method according to claim 6, wherein the polymer latex is an anionic polymer latex.

8. The method of claim 7, wherein the anionic polymer latex comprises one or more of the following: styrene-butadiene, polyolefin, styrene acrylate, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyurethane, epoxy resin, polyester, polyolefin, and carboxylated styrene-butadiene.

9. The method according to any one of the preceding claims, wherein the solids content of the aqueous barrier coating is from about 5% to about 55%.

10. The method according to any one of the preceding claims, wherein high-shear mixing is performed at a tip speed of about 655 ft / min to about 3300 ft / min (200 m / min to 1010 m / min).

11. The method according to any one of the preceding claims, wherein the dry powder of the chemically unmodified sodium-based bentonite contains less than 12% moisture.

12. The method according to any one of the preceding claims, wherein a Cowles mixer, an ultrasonic mixer, or a rotor-stator mixer is used for high-shear mixing.

13. The method of claim 12, wherein an ultrasonic instrument is used for high-shear mixing.

14. The method of claim 13, wherein the ultrasonic treatment lasts for about 1 minute to about 40 minutes.

15. The method according to any one of the preceding claims, wherein the high-shear mixing is performed under conditions for peeling off the sodium bentonite while dispersing the sodium bentonite in the binder, such that the shape factor of the sodium bentonite present in the coating is greater than 4, as measured by Horibard using static light scattering. 50 The ratio of the size of the Zave particles to the size measured by dynamic light scattering was used.

16. The method according to any one of the preceding claims, wherein the dry powder of the chemically unmodified sodium bentonite is added to the binder in an amount of about 1 wt% to about 20 wt% based on the total weight of the mixture on a dry weight basis.

17. The method according to any one of the preceding claims, wherein the mixture does not contain a dispersant.

18. The method according to any one of the preceding claims, wherein the chemically unmodified sodium bentonite is chemically and mechanically unmodified sodium bentonite.

19. A method for preparing a barrier coating for a paper substrate, the method comprising: The dry powder of chemically unmodified sodium-based bentonite is mixed with a binder; The mixture is subjected to high-shear mixing under conditions that disperse the sodium-based bentonite in the binder and at least a portion of the sodium-based bentonite remains in a crystalline aggregate form, thereby forming the barrier coating; and At approximately 1.5g / m 2 Approximately 25g / m 2 The coating weight is obtained by coating the paper substrate with the barrier coating. The adhesive is water-based or water-soluble.

20. The method of claim 19, wherein the coating weight is less than 10 g / m². 2 .

21. The method according to claim 19 or 20, wherein the paper substrate is solid bleached sulfate (SBS) paper, folding boxboard (FBB), white-faced boxboard (WTL), low-basic-weight packaging paper, copy paper, coated or uncoated paper and paperboard, coated unbleached kraft paper (CUK), or coated recycled paperboard.

22. The method according to any one of claims 19 to 21, wherein the adhesive comprises a polymeric latex.

23. The method of claim 22, wherein the polymer latex is an anionic polymer latex.

24. The method of claim 23, wherein the anionic polymer latex comprises one or more of the following: styrene-butadiene, polyolefin, styrene acrylate, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyurethane, epoxy resin, polyester, polyolefin, and carboxylated styrene-butadiene.

25. The method according to any one of claims 19 to 24, wherein the adhesive comprises one or more of the following: carboxylated styrene acrylate latex, polyvinylidene chloride, polyvinyl chloride, starch, styrene-acrylic acid copolymer, styrene-maleic anhydride, polyvinyl alcohol, polyvinyl acetate, carboxymethyl cellulose, silicone, wax, chloroprene rubber, polyhydroxy ether, varnish, polylactic acid, polylactic acid copolymer, fluorine-containing polymer, acrylonitrile copolymer, and carboxylated styrene-butadiene-acrylonitrile copolymer.

26. The method according to any one of claims 19 to 25, wherein the solid content of the water-based barrier coating is from about 5% to about 55%.

27. The method according to any one of claims 19 to 26, wherein high-shear mixing is performed at a tip speed of about 655 ft / min to about 3300 ft / min (200 m / min to 1010 m / min).

28. The method according to any one of claims 19 to 27, wherein the dry powder of the chemically unmodified sodium-based bentonite contains less than 12% moisture.

29. The method according to any one of claims 19 to 28, wherein a Coles mixer, an ultrasonic mixer, or a rotor-stator mixer is used for high-shear mixing.

30. The method of claim 29, wherein an ultrasonic instrument is used for high-shear mixing.

31. The method of claim 30, wherein the ultrasonic treatment lasts for about 1 minute to about 40 minutes.

32. The method according to any one of claims 19 to 31, wherein the high-shear mixing is performed under conditions for peeling off the sodium-based bentonite while dispersing the sodium-based bentonite in the binder, such that the shape factor of the sodium-based bentonite present in the coating is greater than 4, as measured by Horibard using static light scattering. 50 The ratio of the size of the Zave particles to the size measured by dynamic light scattering was used.

33. The method according to any one of claims 19 to 32, wherein the dry powder of the unmodified sodium bentonite is added to the binder in an amount of about 1 wt% to about 20 wt% based on the total weight of the mixture on a dry weight basis.

34. The method according to any one of claims 19 to 33, wherein the mixture does not contain a dispersant.

35. The method according to any one of claims 19 to 34, wherein the chemically unmodified sodium bentonite is chemically and mechanically unmodified sodium bentonite.

36. A water-based barrier coating comprising: Chemically unmodified sodium bentonite dispersed in an adhesive, wherein the sodium bentonite is dispersed under high shear conditions such that at least a portion of the sodium bentonite exists in the form of crystalline aggregates, wherein the adhesive is water-based or water-soluble.

37. The coating of claim 36, wherein the shape factor of the sodium-based bentonite is greater than 4, as measured by Horizontal scattering. 50 The ratio of the size of the Zave particles to the size measured by dynamic light scattering was used.

38. The coating of claim 36 or 37, wherein the adhesive comprises a polymeric latex.

39. The coating of claim 38, wherein the polymer latex is an anionic polymer latex.

40. The coating of claim 39, wherein the anionic polymer latex comprises one or more of the following: styrene-butadiene, polyolefin, styrene acrylate, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, polyurethane, epoxy resin, polyester, polyolefin, and carboxylated styrene-butadiene.

41. The coating according to any one of claims 36 to 40, wherein the adhesive comprises one or more of the following: carboxylated styrene acrylate latex, polyvinylidene chloride, polyvinyl chloride, starch, styrene-acrylic acid copolymer, styrene-maleic anhydride, polyvinyl alcohol, polyvinyl acetate, carboxymethyl cellulose, silicone, wax, chloroprene rubber, polyhydroxy ether, lacquer, polylactic acid, polylactic acid copolymer, fluorine-containing polymer, acrylonitrile copolymer, and carboxylated styrene-butadiene-acrylonitrile copolymer.

42. The coating according to any one of claims 36 to 41, wherein the solids content of the water-based barrier coating is from about 5% to about 55%.

43. The coating according to any one of claims 36 to 42, wherein the sodium-based bentonite is present in the coating in an amount of about 1 wt% to about 20 wt% based on the total weight of the coating on a dry weight basis.

44. The coating according to any one of claims 36 to 43, wherein the coating is free of dispersant.

45. The coating according to any one of claims 36 to 44, wherein the solid content of the coating is equal to or greater than the solid content of the adhesive.

46. ​​A barrier-coated paper substrate comprising a paper substrate coated with a coating according to any one of claims 36 to 45.

47. The barrier-coated paperboard according to claim 46, wherein the paperboard is solid bleached sulfate (SBS) paper, folding boxboard (FBB), white-faced boxboard (WTL), low-basic-weight packaging paper, copy paper, coated or uncoated paper and paperboard, coated unbleached kraft paper (CUK), or coated recycled paperboard.

48. The barrier-coated paper substrate according to claim 46 or 47, wherein the coating weight is less than 10 g / m². 2 And the permeability is less than 400g / m 2 / d.